The Ripple Effect Gender and Race in Brazilian Culture and Literature - José Somerlate Barbosa, Maria (Purdue Studies in Romance Literatures, 2023)
In The Ripple Effect: Gender and Race in Brazilian Culture and Literature, Barbosa adopts a comparative, multilayered, and interdisciplinary line of research to examine social values and cultural mores from the first decades of the twentieth century to the present. By analyzing the historical, cultural, religious, and interactive space of Brazil's national identity, The Ripple Effect surveys expressive cultures and literary manifestations. It uses the martial art-dance-ritual capoeira as a lynchpin to disclose historical ambiguities and the negotiation of cultural and literary boundaries within the context of the ideological construct of a mestizo nation. The book also examines laws governing gender in Brazil and discusses honor killings and other types of violence against women. The Ripple Effect appraises the contributions that some iconic female figures have made to the development of Brazil's distinctive cultural and literary production. Drawing on more than fifteen years of field, archival, and scholarly research, this work offers new interpretative venues, and broadens the critical focus and the methodological scope of previous scholarship. It reveals how literature and other arts can be used to document cultural norms, catalog life experiences, and analyze complex constructions of social values, ideas, and belief systems.